2008
DOI: 10.1016/j.leukres.2008.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Lethality to leukemia cell lines of DNA interstrand cross-links generated by Cloretazine derived alkylating species

Abstract: Cloretazine [1, 2-bis(methylsulfonyl)-1-(2-chloroethyl)-2-[(methylamino)carbonyl]-hydrazine; VNP40101M; 101M] is a relatively new prodrug with activity in elderly acute myelogenous leukemia patients. Its therapeutic action is due largely to the production of 1-(3-cytosinyl),2-(1-guanyl)ethane cross-links (G-C ethane cross-links) in DNA. The number of cross-links produced in three experimental leukemia lines (L1210, U937 and HL-60) were fewer than 10 per genome at their respective LC 50 concentrations. Only 1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
95
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(99 citation statements)
references
References 33 publications
4
95
0
Order By: Relevance
“…18,20,21 The preclinical development of laromustine was focused on the synthesis of an agent that generated an alkylating species that demonstrated antitumor activity with relatively less toxicity to normal tissues. 5,[7][8][9][10]27,28 The clinical development of laromustine in AML has evolved from a consistent demonstration, in both adult and pediatric patients with a variety of refractory solid tumors or hematologic malignancies, that myelosuppression is the dose-limiting toxicity, occurring at doses that incur relatively low extramedullary toxicity. [16][17][18][19][20][21] In 2002, after analysis of 31 trials of at least 20 patients each, Leopold and Willemze concluded that no chemotherapy regimen had been shown to be more effective than another for patients with relapsed AML.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…18,20,21 The preclinical development of laromustine was focused on the synthesis of an agent that generated an alkylating species that demonstrated antitumor activity with relatively less toxicity to normal tissues. 5,[7][8][9][10]27,28 The clinical development of laromustine in AML has evolved from a consistent demonstration, in both adult and pediatric patients with a variety of refractory solid tumors or hematologic malignancies, that myelosuppression is the dose-limiting toxicity, occurring at doses that incur relatively low extramedullary toxicity. [16][17][18][19][20][21] In 2002, after analysis of 31 trials of at least 20 patients each, Leopold and Willemze concluded that no chemotherapy regimen had been shown to be more effective than another for patients with relapsed AML.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Laromustine (Onrigin, VNP40101M; Vion Pharmaceuticals Inc) is a sulfonylhdrazine alkylating agent selected for clinical development based on its broad antitumor activity in preclinical models. [4][5][6] Activated, it forms a chloroethylating group that preferentially targets the O 6 over the N 7 position of guanine, resulting in interstrand DNA cross-links. 7 In vitro, it produces more cross-links and fewer DNA single-strand nicks compared with carmustine and lomustine.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations